2011
DOI: 10.1007/s00464-011-1639-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative assessment of biliary anatomy for prevention of bile duct injury: a review of current and future patient safety interventions

Abstract: BackgroundBile duct injury (BDI) is a dreaded complication of cholecystectomy, often caused by misinterpretation of biliary anatomy. To prevent BDI, techniques have been developed for intraoperative assessment of bile duct anatomy. This article reviews the evidence for the different techniques and discusses their strengths and weaknesses in terms of efficacy, ease, and cost-effectiveness.MethodPubMed was searched from January 1980 through December 2009 for articles concerning bile duct visualization techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 82 publications
(127 reference statements)
1
94
0
9
Order By: Relevance
“…Despite variation on opinions about the routine or selective use of IOC, it has demonstrated a reduction in the incidence of major BDI and expeditiously identifies insults at the time of surgery [2,13,52,59,[70][71][72][73]. Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %.…”
Section: Importance Of Intraoperative Detection Of Bdimentioning
confidence: 84%
“…Despite variation on opinions about the routine or selective use of IOC, it has demonstrated a reduction in the incidence of major BDI and expeditiously identifies insults at the time of surgery [2,13,52,59,[70][71][72][73]. Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %.…”
Section: Importance Of Intraoperative Detection Of Bdimentioning
confidence: 84%
“…[5][6][7][8][9][10]15 The contrast leak in the surgical field may result in poor image quality, especially when small ducts are being evaluated. Also, owing to the 2D nature of the image, accurate identification of 2 overlapping liver segments is very diffi cult.…”
Section: Discussionmentioning
confidence: 99%
“…Special attention should be paid to the learning curve for interpreting IOC, as some studies report high proportions of incorrectly interpreted cholangiograms. For example, Way et al [7] demonstrated that 34/43 (79%) routine cholangiograms that showed bile duct injury were incorrectly interpreted [1]. Woods et al reported 53 patients, Incorrect interpretation of the IOC occurred in at least eight patients, with no identification of the proximal biliary tree in six [8].…”
Section: Discussionmentioning
confidence: 99%
“…LIOC is the most frequently applied technique for intraoperative assessment of the biliary anatomy [1]. LIOC is a dynamic procedure; the only real advantage to the surgeon is being able to view the IOC, and specifically the character and movement of any filling defect in real-time, which aids the interpretation of whether there is a stone or air bubble.…”
Section: Introductionmentioning
confidence: 99%